قياس وتحلیل أثر ألادوات الكمية للسياسة النقدية على حجم الائتمان المصرفي في العراق للمدة (2004-2020) - غفور, أ. م. د. نەرمين معروف; عبدالله, نيشتيمان ئارام (Sulaimani Journal for Humanities, 2023)
This research aims to identify the most effective quantitative monetary policy tools to control the volume of bank credit in Iraq during the period of (2004-2020). To achieve this objective, the research measures the impact of explanatory variables, (the Reserve Requirement, the Discount Rate, and open market operations), on the dependent variable (the amount of bank credit) the autoregressive distributed lag (ARDL) method was adopted, and the research reached a set of conclusions, including the existence of a medium inverse relationship between the two tools (Discount Rate and statutory cash reserve ratio) and total volume of bank credit in Iraq and a positive relationship between the (open market operations) and total volume of credit and the results showed that the most effective quantitative tool for monetary policy in affecting the bank credit volume was the re-Discount Rate tool, and In the second place, the Reserve Requirement has a clear impact on the volume bank credit, while the open market operations effects came on the volume bank credit, And It showed that the reverse impact of the Reserve Requirement on total bank credit in the short term will continue and increase in the long term. As for the reverse effect, the re-Discount Rate decreasing in the long run, in light of these results and in order to achieve the desired results from the use of monetary policy tools, the monetary authority must coordinate between the qualitative and quantitative tools in terms of ratio and timing so that their results do not conflict with each other. Activating and revitalizing the stock market by providing a legal and economic environment and scientific and technical expertise. Encouraging private banks to expand their activities and their participation in economic development by employing their superior liquidity in granting credit. And also adopting a strategy that directs credit to the development of productive sectors that serve the economy and contribute to its growth, and to overcome cases of reservation in granting bank credit.
Keywords: Monetary policy; Reserve Requirement; Discount Rate; Open Market Operations; Bank Credit